DEVELOPING OF VIRGIN AND UNUSED LANDS IN KOSTANAY REGION - Айсина, А.; Абильмаликов, К. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2015)
In article authors tried to consider the beginning of the period of deve-lopment of a virgin soil in the Kostanay region, region where virgin lands became a basis of zernovodchesky economy of edge in modern time. To show that spirit, enthusiasm of the first pervotselinnik, economic recovery in the region, here one of main goals of this article. In article also there is also information on the first woman to a traktoristka Kamshat Donenbayevoy, the woman – the Hero of Socialist work.
Keywords: Kostanay history region; heros social work; Developing of virgin and Unused Lands; collective ferm and state ferme